2013
DOI: 10.1002/pros.22668
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of androgen‐responsive genes and transforming growth factor‐β1 cascade genes in a rat model of non‐bacterial prostatic inflammation

Abstract: Background Prostatic inflammation is associated with the development of prostatic hyperplasia. We investigated the effects of prostatic inflammation on expression levels of androgen-responsive genes and growth factors in the prostate. Methods Prostatic inflammation was induced by formalin injection into bilateral ventral lobes of the prostate of male SD rats. After 28 days, the prostate was harvested for analyses of proinflammatory cytokines, androgen-responsive genes in the epithelium and TGF-β1 cascade gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
35
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 33 publications
5
35
1
Order By: Relevance
“…In addition, the rat model of prostatic inflammation used in this study is not the direct model of BPH; however, we have shown that this rat model exhibits the upregulation of androgen receptor‐responsive genes and TGF‐β‐related genes in the prostate (Funahashi et al . ), which is similarly seen in human BPH tissues (O'Malley et al . ), and that increased IL‐18 expression induced by inflammasome activation is similarly found in the formalin‐induced rat prostatic inflammation model (Kashyap et al .…”
Section: Discussionsupporting
confidence: 58%
“…In addition, the rat model of prostatic inflammation used in this study is not the direct model of BPH; however, we have shown that this rat model exhibits the upregulation of androgen receptor‐responsive genes and TGF‐β‐related genes in the prostate (Funahashi et al . ), which is similarly seen in human BPH tissues (O'Malley et al . ), and that increased IL‐18 expression induced by inflammasome activation is similarly found in the formalin‐induced rat prostatic inflammation model (Kashyap et al .…”
Section: Discussionsupporting
confidence: 58%
“…2, 6, 7 Cytokines secreted from inflammatory cells stimulate androgen receptor activity in prostate cancer cells. 22, 23 We have previously reported molecular changes similar to those identified in human BPH specimens in an abacterial rat model of prostatitis, 18 which is characterized by infiltration of inflammatory cells up to 4 weeks after intraprostatic formalin injection. In this study, we further demonstrated that E. coli-induced chronic inflammation also induces the long-lasting (12 weeks) upregulation of epithelial androgen-responsive and stromal TGF-β1 cascade genes.…”
Section: Discussionmentioning
confidence: 78%
“…18 In this study, we evaluated whether chronic prostatic inflammation for 12 weeks induces the elevated expression of androgen and TGF-β1 cascade genes and assessed the effects of a COX-2 inhibitor on the expression of these genes using a rat model of bacterial prostatitis.…”
Section: Introductionmentioning
confidence: 99%
“…Group V: BPH+CLX as a positive control (received 10 mg/kg celecoxib in combination with TP s.c by gavage) (20). …”
Section: Methodsmentioning
confidence: 99%